THE CORRELATION BETWEEN THE INTEREST OF LEARNING AND FACILITIES LEARNING WITH THE STUDENT’S MATHEMATICS LEARNING OUTCOME - RR Sri Handayani; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Students are learning mathematics results to relate to many factors. Interest in learning, learning independence, and learning a facility are some of the factors suspected to be related to learning outcomes. This study aims to determine whether there is a positive and significant relationship between interest in learning and learning facilities with the results of a learning mathematics students grade VIII SMP in odd semester of the year 2017/2018 academic.  The population in this study are all students of class VII odd semester  of State Junior High School (SMP Negeri) 3 Pajangan Bantul in the academic year 2017/2018, consisting of four classes with 131 students. Samples were taken by random sampling technique and obtained class VIII C consisting of 33 students. Data collection techniques used questionnaires and test techniques. Test of research instrument using validity test, reliability test, and test of different power. Existence prerequisite tests include normality tests, independent tests, and linearity tests.  To analysis the data, the researcher using correlation analysis and linear regression analysis. The results showed that there was a positive and significant correlation between learning interest (X1) and learning facility (X2) with students' mathematics learning result with Fcount > Ftable ie 4.7837> 3.32 with R = 0.4917 and R2 = 0.2418 with Y = -1,8047 + 0,1724X1 + 0,5499X2, and RC (X1) = 18,9191 % and RC (X2) = 81,0809%, EC (X1) = 04,4309% and EC (X2) = 18.9891%.